Historiographical Revisionism and Re-Articulation of Memory in the Former Yugoslav Republic of Macedonia - Marinov, Tchavdar (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2010)
This article examines the profound reshaping of memory politics in the Republic of Macedonia since independence. Tchavdar Marinov shows how the dismantling of communist historiography opened the way for competing reinterpretations of the past, mobilized by various actors — historians, activists, veterans, and political leaders — to legitimize opposing national positions. The debates revolve around the legacy of the communist movement, the rehabilitation of nationalist IMRO figures, and the challenge of articulating a Macedonian identity no longer grounded in the Yugoslav experience. Faced with these tensions, the authorities gradually embraced an “ancient” memory centered on Alexander the Great, intended to transcend recent divisions. The article thus demonstrates how the construction of the past has become a key arena of political competition in post-Yugoslav Macedonia. Révisionnisme en historiographie et réarticulation de la mémoire dans l'ancienne République yougoslave de Macédoine Cet article analyse les profondes recompositions des politiques de la mémoire en République de Macédoine depuis l’indépendance. Tchavdar Marinov montre comment la remise en cause de l’historiographie communiste a ouvert la voie à des révisions concurrentes du passé, mobilisées par des acteurs variés — historiens, militants, vétérans, responsables politiques — pour légitimer des positions nationales opposées. Les débats portent à la fois sur l’héritage du mouvement communiste, la réhabilitation des figures nationalistes de l’IMRO et la difficulté à articuler une identité macédonienne non adossée à l’histoire yougoslave. Face à ces tensions, les autorités ont progressivement investi une mémoire « antique » centrée sur Alexandre le Grand, censée transcender les clivages récents. L’article montre ainsi comment la fabrique du passé devient un terrain central de compétition politique dans la Macédoine post-yougoslave.